Encoding bamboo's nature for freeform structure design. (June 2017) - Wang, Tsung-Hsien; Espinosa Trujillo, Olivia; Chang, Wen-Shao; Deng, Bailin
Bamboo is a construction material that is renewable, environmentally friendly and widely available. It has long been used in various projects, ranging from temporary, easily assembled and rectilinear structures to complex freeform pavilions. Design with bamboo has never been easy to architects and engineers due to its irregular shape and round section. This prompts the need to develop a new design process that can accommodate those properties that hinder bamboo to be used by designers. In this article, we take a close look at freeform structure design and specifically demonstrate how systematically and algorithmically parametric modelling can be used to tackle bamboo material irregularities and bamboo jointing challenges. A two-stage optimization process is proposed to support a fabricable freeform structure design through encoding material properties and freeform shape optimization. The approach approximates the given freeform shape using a finite set of unique bamboo elements while maintaining the aesthetic design intention. By limiting the number of bamboo elements, it will provide insight to both designers and engineers on the efficiency and cost benefits of producing required structure elements for the final assembly.